Influence of User Satisfaction of the Halodoc Mobile Application using the End User Computing Satisfaction (EUCS) and DeLone and McLean methods - Wulandari, Suri; Munzir, Medyantiwi Rahmawita; Rozanda, Nesdi Evrilyan; Zarnelly, Zarnelly (Sistemasi: Jurnal Sistem Informasi, 2024)
PT. Media Dokter Investama is one of several technology companies that provides health consultation services in Indonesia through Mobile Health Technology (MHealth Tech) products. Mobile application. It was recorded that in October 2023 the Halodoc application on Playstore received a rating of 4.8 on a scale of 5 with more than 426 thousand reviews from users. The level of use of the Halodoc application is very high, giving rise to several negative ratings. As in the reviews from rating 2 or not liking the application as much as 658 or 5.76%, and rating 1 or really not liking the application as many as 1,577 reviews or 13.78%. From these results it can be seen that there are still some users who are dissatisfied with the Halodoc application. This research was conducted to measure the influence of user satisfaction of the Halodoc application using the End User Computing Satisfaction and DeLone and McLean methods and to provide research recommendations which can be an input for Halodoc application managers to manage and improve the Halodoc application in the future.